Insider investing for real estate agents : - Sanford, Walter S. (Wiley, 2006)
In this one-of-a-kind guide, Walter Sanford shows you not only how your experience as an agent can aid your investing, but also how investing can make you a better agent--leading to more customers, listings, and sales. Filled with all the tools you need to combine and improve your skills as an investor and agent, this practical, hands-on resource includes more than 100 handy forms, checklists, and worksheets--all designed to help you make wise decisions, spot bargains, and manage properties with a minimum of risk. Inside, you'll find unbeatable advice on: Insider tactics for obtaining investment financing; Using your natural advantages as an agent to find great properties; Working honestly and ethically as both an agent and an investor; Tapping into your lead generation skills to invest better; Performing due diligence the way only an agent can; Insider tenant acquisition tactics that really work.